KANTIAN EPISTEMOLOGY IN EXAMINATION OF THE AXIOMATIC PRINCIPLES OF ECONOMICS: THE SYNTHETIC A PRIORI IN THE ECONOMIC BEHAVIOR/STRUCTURE OF SOCIETY - Adil Ahmad Mughal (International Journal of Contemporary Issues in Social Sciences, 2024)
The axioms of Economic theory combine mathematical formalism with behaviorally stable and reproducible patterns. This paper sees this synthesis as a Kantian synthetic a priori method quantified on prices and revealed preferences. The intuitions as inherently continuous magnitudes in Critique of Pure Reason just sit so well inside the convexity and continuity assumptions in Economics. This aspect of intuitions facilitates a raw economic behavior to be synthesized into formal Economic theory. This paper demonstrates Kant's synthetic a priori criterion to be implied in the axiomatic Economics.